The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1093/carcin/9.3.485
|View full text |Cite
|
Sign up to set email alerts
|

A mammalian cell mutant with enhanced capacity to dissociate a bis-benzimidazole dye-DNA complex

Abstract: The bis-benzimidazole dyes (specifically Hoechst 33258 and the more lipophilic derivative Hoechst 33342) are non-intercalating AT base pair-specific ligands which bind to cellular DNA by non-covalent association with the minor groove. The interaction of dye with cellular DNA is thought to be the principal pathway for the cytotoxic, mutagenic and DNA-damaging properties of such agents. Upon binding and near UV light excitation, dye molecules exhibit fluorescence enhancement such that dye/DNA association and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Ltk-mouse cell line was developed from a subline of the BrdU-resistant strain of the L-M mouse line (Kit et al, 1963). The Ltk-drug-selected subline (Ltk-HoeR415) has been shown to have increased Abcg2 expression and function (Smith et al, 1988(Smith et al, , 2009 mice, and the MEF3.8 M32 subline were provided by Alfred H. Schinkel (Netherlands Cancer Institute). The human ABCG2-expressing sublines used (H460 MX20 and MCF7 FLV500) have been previously characterized (Robey et al, 2001b(Robey et al, , 2004.…”
Section: Methodsmentioning
confidence: 99%
“…The Ltk-mouse cell line was developed from a subline of the BrdU-resistant strain of the L-M mouse line (Kit et al, 1963). The Ltk-drug-selected subline (Ltk-HoeR415) has been shown to have increased Abcg2 expression and function (Smith et al, 1988(Smith et al, , 2009 mice, and the MEF3.8 M32 subline were provided by Alfred H. Schinkel (Netherlands Cancer Institute). The human ABCG2-expressing sublines used (H460 MX20 and MCF7 FLV500) have been previously characterized (Robey et al, 2001b(Robey et al, , 2004.…”
Section: Methodsmentioning
confidence: 99%
“…In this field, recent NMR spectroscopic studies demonstrated that moving the phenolic -OH group of Hoechst 33258 from the para to the meta position provides an additional hydrogen bond between the m -OH and DNA (Parkinson et al, 1994). Controversially, the ethoxy derivative of the phenolic -OH group of Hoechst 33258, named Hoechst 33342, has a lower affinity for DNA than the parent drug (Smith et al, 1988).…”
mentioning
confidence: 99%
“…Emission spectrum analysis using narrow band‐pass filters (centered at 400, 450, 500, 555, and 600 nm wavelengths) reveals that dye–DNA dissociation during the incubation of mammalian cells in dye‐free medium results in preferential loss of red versus violet fluorescence. The reverse spectral shift is accelerated when overall dye efflux is enhanced 10‐fold by specific overexpression of ABCG2 (19, 54). This kinetic relationship can be exploited to identify moribund cells which show an “instantaneous” and distinct red‐biased Hoechst 33342–DNA emission signature (55) due to ready access of dye to DNA binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach is useful for the FACS isolation of rare SP cells that may require extended instrument run‐times. However, an early study has shown ongoing efflux in SP‐like cells has an initial T ½ of significantly <30 min for the loss of red fluorescence, allocating non‐SP cells to an SP fraction, highlighting the need to control the potential for on‐going dye wash‐out (54).…”
Section: Resultsmentioning
confidence: 99%